Depressive symptoms in the oldest-old: The role of sensory impairments. (September 2018) - Cimarolli, Verena R.; Jopp, Daniela S.; Boerner, Kathrin; Minahan, Jillian
Highlights: Vision impairment is associated with more depressive symptoms among oldest-old individuals. Hearing impairment alone is not associated with depressive symptoms among oldest-old. Concurrent vision and hearing impairment results in the highest depressive symptoms. Functional disability, health interference, and loneliness are also associated with depression. Abstract: Background: While a fair amount of research has investigated the impact of sensory impairments on the mental health of young older adults (65–79 years of age), only a few studies have focused on the associations of sensory impairments with mental health outcomes in the oldest-old (80 years and older). To close this gap, this study examined the separate and combined effects of self-reported vision and hearing impairment for depressive symptoms in a sample of oldest-old individuals, controlling for other mental health risks (e.g., functional disability, health interference, and loneliness). Methods: Centenarians and near-centenarians (N = 119; average age = 99) were recruited from the community and geriatric healthcare organizations. In-person interviews were conducted at participants' place of residence. Results: Vision impairment and its interaction with hearing impairment as well as functional disability, health interference with desired activities, and loneliness were significant predictors of depressive symptoms in hierarchical regression analyses. Hearing impairment alone was not associated with depressive symptoms, but follow-up analyses clarifying the interaction effect showed that individuals with poor vision had the highest levels of depressive symptoms, if they had a concurrent hearing impairment. Thus, a concurrent presence of poor vision and poor hearing resulted in an increased vulnerability for depressive symptoms. Conclusions: Given that a majority of oldest-old has sensory impairments which can result in mental health issues, it is important to facilitate this population's access to vision and audiological treatment and rehabilitation.